How Do IT Governance Practices In Indonesian Public and Private Sectors? Evidence From The Literature - Wahyudi Agustiono (Journal of International Conference Proceedings (JICP), 2018)
This paper sought to understand the IT governance practices among public and private organisations in Indonesia. To address this aim, it mainly identifies and examines articles from both academia and practitioners reporting empirical evidence about IT governance practices in Indonesia. This paper, in doing so, makes three important contributions. First, it shows what current state the art of IT governance practices in Indonesia. Second, it offers practical implications by reporting and discussing the experiences, best practices, lessons learned challenges, and the different factors influencing IT governance practices in Indonesian public and private sectors. Finally, by undertaking such systematic review on the literature, it also attempts to identify the gap in knowledge from which future research can address. Keywords: IT Governance, Literature Review, Public and Private sector